Sociolinguistic aspects in teaching Italian to foreigners: Array - Botezatu, Vanina Narcisa; Nicolae, Gabriela Florentina (Acta Universitatis Danubius. Communicatio, 2021)
This article briefly refers to the use of sociolinguistic aspects in the acquisition and teaching of the Italian language to foreigners. It emphasizes the need for full teaching so that the student assimilates, in addition to language forms, all the socio-cultural aspects needed to achieve full training. It is therefore important not only to be able to understand the language but also to be able to juggle effectively and with efficiency in the social and not just individual use of the language.